Cheirogaster sp. (O. Testudines, Fam. Testudinidae, Geochelone sl.) du Paléogène de Naia, Tondela et l’âge du gisement - Antunes, M. Telles (2008)
A land tortoise from a new locality at Naia, Tondela, is described. It is to be reported either to an advanced form of the genus Hadrianus or to an archaic representative of Cheirogaster; it may be included in the comprehensive genus Geochelone s.l., excluding however Ergilemys and its descendants. There is a strong possibility in favour of Cheirogaster. Testudo must also be excluded. It is not possible to classify this specimen at species'level. Our specimen does agree best with Upper Eocene Testudinidae and with some Lower Oligocene ones. Its age is certainly not Upper Oligocene or later, nor Lower and Middle Eocene. This datation is not opposed to the age of the fossiliferous clays of Naia as supposed by correlation with another locality - Côja, about 30 km to the South - which yielded an assemblage of mammals whose Ludian (Upper Bartonian s.l.) age seems well established. Naia and Côja's fossil-bearing clays must be nearly synchronous; their origin is well in place among the phenomena related to the surrection of iberian Central Chain during paroxysmal phase of pyrenean orogenesis.